Editorial - Vieira, Wilson; Capêda, Vera Alves; de Malta, Maria Mello (Cadernos do Desenvolvimento, 2024)
Editoria. Cadernos do Desenvolvimento, Centro Internacional Celso Furtado, v. 18, n. 34, jan.-abr. 2023.